2016
DOI: 10.2967/jnumed.116.185538
|View full text |Cite
|
Sign up to set email alerts
|

PSA-Stratified Performance of 18F- and 68Ga-PSMA PET in Patients with Biochemical Recurrence of Prostate Cancer

Abstract: Several studies outlined the sensitivity of Ga-labeled PET tracers against the prostate-specific membrane antigen (PSMA) for localization of relapsed prostate cancer in patients with renewed increase in the prostate-specific antigen (PSA), commonly referred to as biochemical recurrence. Labeling of PSMA tracers withF offers numerous advantages, including improved image resolution, longer half-life, and increased production yields. The aim of this study was to assess the PSA-stratified performance of the F-labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
186
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(202 citation statements)
references
References 21 publications
(98 reference statements)
10
186
0
6
Order By: Relevance
“…In a head-to-head comparison in 14 patients with recurrent PC, staging with 18 F-DCFPyL PET/CT was equivalent to that with 68 Ga-PSMA-11 (44). A follow-up study from the same group using PSA-adjusted parallel biochemically recurrent PC patient cohorts (including a total of 191 patients) found that 18 F-DCFPyL was noninferior to 68 Ga-PSMA-11 (45) and suggested an improved sensitivity of the 18 F-labeled radiotracer in the PSA range of 0.5-3.5 ng/mL (with the caveat that different injected doses and acquisition parameters were used for the 2 PSMA-targeted agents). Further indepth clinical studies with standardized acquisition protocols and histologic validation are needed to establish the comparative performance of these 2 radiotracers.…”
Section: Main Clinical Indications Of Psma Ligand Pet/ct and Current mentioning
confidence: 99%
“…In a head-to-head comparison in 14 patients with recurrent PC, staging with 18 F-DCFPyL PET/CT was equivalent to that with 68 Ga-PSMA-11 (44). A follow-up study from the same group using PSA-adjusted parallel biochemically recurrent PC patient cohorts (including a total of 191 patients) found that 18 F-DCFPyL was noninferior to 68 Ga-PSMA-11 (45) and suggested an improved sensitivity of the 18 F-labeled radiotracer in the PSA range of 0.5-3.5 ng/mL (with the caveat that different injected doses and acquisition parameters were used for the 2 PSMA-targeted agents). Further indepth clinical studies with standardized acquisition protocols and histologic validation are needed to establish the comparative performance of these 2 radiotracers.…”
Section: Main Clinical Indications Of Psma Ligand Pet/ct and Current mentioning
confidence: 99%
“…17,18 Furthest along in clinical development is the 18 F-DCFPyL radiotracer, which was first described by Chen et al 19 This radiotracer has been examined in several studies in the context of imaging biochemically recurrent or metastatic PCa. 2022 …”
mentioning
confidence: 99%
“…In the remaining patient (case 5), known bone metastases showed very low uptake of 18 F‐FSU‐880 with a TBR < 1 at all time points. It is reported for 68 Ga‐ and 18 F‐labeled PSMA probes that, in biochemical recurrence, patients with low serum PSA levels showed a low detection rate . When PET/CT was carried out at very early stage with low PSA level, the lesion size was too small to be detected due to partial‐volume effect.…”
Section: Discussionmentioning
confidence: 78%